2018
DOI: 10.1016/j.renene.2018.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different methods for determining the angle of attack on wind turbine blades with CFD results under axial inflow conditions

Abstract: This work presents an investigation on different methods for the calculation of the angle of attack and the underlying induced velocity on wind turbine blades using data obtained from three-dimensional Computational Fluid Dynamics (CFD). Several methods are examined and their advantages, as well as shortcomings, are presented. The investigations are performed for two 10MW reference wind turbines under axial inflow conditions, namely the turbines designed in the EU AVATAR and INNWIND.EU projects. The results sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 27 publications
4
47
0
Order By: Relevance
“…This is not the case for AAT; thus, we consider the results obtained with the new method to be more realistic. This interpretation is supported by the results of two different turbines presented in Rahimi et al (2018), who show that the method proposed by Shen et al (2006), which presents the advantage of computing the local blade velocities more accurately, is in excellent agreement with our method in the root and tip region, and it also deviates considerably from the AAT.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…This is not the case for AAT; thus, we consider the results obtained with the new method to be more realistic. This interpretation is supported by the results of two different turbines presented in Rahimi et al (2018), who show that the method proposed by Shen et al (2006), which presents the advantage of computing the local blade velocities more accurately, is in excellent agreement with our method in the root and tip region, and it also deviates considerably from the AAT.…”
Section: Resultssupporting
confidence: 80%
“…A comparison of several methods for obtaining them concluded that three out of four methods were reasonably consistent and reliable (Guntur et al, 2011). In a very recent benchmark study of multiple methods for computing the AoA (including the one presented here), similar results were obtained from all methods except at the tip and root of the blade, where substantial disagreement between some methods was found (Rahimi et al, 2018). A detailed description of all the existing methods is out of the scope of this article, although the reader is referred to Guntur et al (2011) and Rahimi et al (2018) for a good overview of the different methods.…”
Section: Available Methodssupporting
confidence: 68%
See 1 more Smart Citation
“…Another option is to use dynamic inductions from the CFD solution to estimate the time constants. However, a recent comparison has shown that there is still considerable uncertainty in induced velocities from CFD towards the root and tip of the blade (Rahimi et al, 2018). This uncertainty complicates the estimation of the radially varying dynamic inflow time constants.…”
Section: Influence Of Pitching Directionmentioning
confidence: 99%
“…In the current study, however, it is neglected as the two verification environments, HAWC2 and EllipSys3D-Flex5, do not model the surface of the airfoils. Shen et al (2006Shen et al ( , 2009, Guntur and Sørensen (2014), and Rahimi et al (2018) present several methods to calculate the flow near the airfoil that also take 3-D effects into account, but the methods require information that cannot be obtained directly from a BMFS. Pedersen et al (2017) describes how to obtain the effective 3-D inflow from the relative wind speed and two perpendicular angles measured by a blade-mounted five-hole pitot, including compensation for bound circulation.…”
Section: Wind Speed From a Bmfsmentioning
confidence: 99%